The role of brain creatine in behavioral health conditions - Han, Ellie S.; Yancey, James R.; Yurgelun-Todd, Deborah A.; Kondo, Douglas G.; Boxer, Danielle J.; Renshaw, Perry F. (Frontiers in Psychiatry, 2025)
Creatine, as a naturally occurring organic compound, has gained attention for its potential role in psychiatric health. The creatine kinase-phosphocreatine energy buffer system plays a crucial role in maintaining energy supply in the brain. Brain bioenergetic deficits, particularly those related to mitochondrial dysfunction, plays a critical role in the pathophysiology of psychiatric illnesses. A growing body of literature has focused on the potential therapeutic role of creatine supplementation in psychiatric illnesses. This review summarizes findings from preclinical, epidemiological, clinical and neuroimaging studies to examine creatine’s role as both a biomarker and therapeutic agent in psychiatric disorders, including Major Depressive Disorder, Anxiety Disorders, Posttraumatic Stress Disorder, and Substance Use Disorder.